2016
DOI: 10.3390/min6020045
|View full text |Cite
|
Sign up to set email alerts
|

Clay Mineralogy of Coal-Hosted Nb-Zr-REE-Ga Mineralized Beds from Late Permian Strata, Eastern Yunnan, SW China: Implications for Paleotemperature and Origin of the Micro-Quartz

Abstract: Abstract:The clay mineralogy of pyroclastic Nb(Ta)-Zr(Hf)-REE-Ga mineralization in Late Permian coal-bearing strata from eastern Yunnan Province; southwest China was investigated in this study. Samples from XW and LK drill holes in this area were analyzed using XRD (X-ray diffraction) and SEM (scanning electronic microscope). Results show that clay minerals in the Nb-Zr-REE-Ga mineralized samples are composed of mixed layer illite/smectite (I/S); kaolinite and berthierine. I/S is the major component among the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Overall, the C25 coals have high concentrations of Nb, Ta, Zr, Hf, and REE, which came mainly from alkali volcanics. The origin of these rare metals in the C25 coal present in this study is similar to those in the coals or coal-bearing sedimentary sequences in the surrounding areas [63][64][65][66][67]. [10] and C19-r; and (B) the coal in Lvshuidong [5] and C25-3.…”
Section: C25 Coals and Volcanic Ashes Of Alkali Rhyolitesmentioning
confidence: 66%
“…Overall, the C25 coals have high concentrations of Nb, Ta, Zr, Hf, and REE, which came mainly from alkali volcanics. The origin of these rare metals in the C25 coal present in this study is similar to those in the coals or coal-bearing sedimentary sequences in the surrounding areas [63][64][65][66][67]. [10] and C19-r; and (B) the coal in Lvshuidong [5] and C25-3.…”
Section: C25 Coals and Volcanic Ashes Of Alkali Rhyolitesmentioning
confidence: 66%
“…Hydrothermal fluid activity plays an important role in the enrichment of mineral matter in the coals not only from southwestern China [2,40,43,[83][84][85][86][87][88], but also from some coal deposits elsewhere [89][90][91]. However, the characteristics and alteration mechanism of hydrothermal solution are not clear.…”
Section: Injection Of Low-temperature Hydrothermal Fluidsmentioning
confidence: 99%
“…Previously studies [29,30,48] showed that the formation of chamosite in eastern Yunnan coals was related to hydrothermal fluids, either deposited from Fe-rich hydrothermal fluids [29] or formed via interaction between kaolinite and Fe-Mg-rich fluids during early diagenesis [30]; (2) Florencite identified in the samples ( Figure 14C). This is a secondary REE-bearing mineral related to hydrothermal fluid [38,86,96]; (3) Fracture-filling siderite ( Figure 9C,D) and fracture-filling calcite in the samples. These carbonate minerals indicate epigenetic solution precipitation; (4) Abundant siderite (65%) and calcite (20%) in sample SGT1-2p.…”
Section: Injection Of Multi-stage Hydrothermal Fluidsmentioning
confidence: 99%